Identification and harmfulness analysis of solid particles contained in medical injections and their removal by nuclear track membranes - Yang, Jian-Xin; He, Zhi-Bo; Guo, Shi-Lun (Perspectives in science, 2019)
Two types of cascade nuclear track filters have been developed: (1) cascade filter made of polypropylene (PP) fiber membrane as preliminary filter and nuclear track membrane (NTM) as terminal filter; (2) Nylon tortuous-pore membrane as preliminary filter and NTM as terminal filter. Removal of solid particles by the cascade filters has been investigated. The solid particles studied include glass shards from broken ampoules and rubber fragments from rubber covers (plugs) of medical bottles. When an ampoule containing medicine is broken by emery wheel and by hands, large number of glass shards are produced and fall into the medicine. When a rubber cover is punctured by syringe needle, large number of rubber fragments are produced by friction between rubber and needle. The investigation shows that fiber or tortuous membranes alone usually cannot completely remove the microscopic particles due to existence of large gaps in the structure of the two common membranes. Nuclear track membranes alone and their cascade filters are superior to remove all solid particles bigger than the pore size of the track membrane. Removal efficiency for solid particles and flow rate of injections through the cascade filters have been calibrated and shown that both features above fulfill the requirements of Chinese regulations. The two types of cascade filters have been accepted for use in Chinese hospitals.